The Mediating role of Majlis Agama Islam Johor/ Mahdzir Md Sirat@Md Siraj, Mohd Asmadi Mohd Angsor, & Zety Shakila Mohd Yusof - Md Sirat@Md Siraj, Mahdzir; Mohd Angsor, Mohd Asmadi; Mohd Yusof, Zety Shakila (2012)
The main purpose of this study is to examine and gain a better understanding of the significant relationships among the determinants of zakat on income and the mediating role of Majlis Agama Islam Johor. It was done among 200 respondents in Johor Bahru. Data which was gathered through questionnaires was analyzed by using statistical package for social science (SPSS) software 20.0. Two types of statistic were used namely descriptive and inferential statistic. Frequency, mean, standard deviation and percentage were the type of statistic descriptive and statistic inferential used were multiple regression and correlation. The result showed that there is a positive influence among the determinants of zakat on income. Result also showed that MAIJ have significant correlations between the determinants of zakat on income. Even MAIJ had been identified as a mediator, but currently its role is still in a weak position as a zakat collector